Populational floating of beds in soybean culture with silicon application in the cerrado-pantanal region of ecotono (Research, Society and Development, 2020)
Soybean (Glycine max L. Merrill) is considered one of the main legumes of modern agriculture, because it has high productive potential and is one of the most important crops that participate in the world economy, mainly due to its wide use and diversification in the system of cultivation. Among the main insects-pests of the crop, are the bedbugs of the Pentatomidae family, especially: Nezara viridula, Euschistus heros, Piezodorus guildinii, Dichelops furcatus and Edessa meditabunda that cause irreversible damage to the crop, from the beginning of pod formation until the final stage of filling of the grains, affecting the yield and the final quality of this product, besides contributing to the foliar retention in the plants. Therefore, this work aims to analyze the population fluctuation of bedbugs in the soybean crop with application of silicon in the cerrado-pantanal ecotone region during the 2015/2016 harvest. The experiment was carried out in the experimental area of the State University of Mato Grosso do Sul - University Unit of Aquidauana (UEMS / UUA), in the field of Phytotechnology, located in the city of Aquidauana-MS. The experimental design was completely randomized blocks containing four replications in a subdivided plots scheme. The plots were represented by the following soybean cultivars: 7166; M6210; M6410; SYN13671; SYN9070; TMG7060, the subplots being subjected to the following treatments: I) without silicon application; II) with application of silicon applied via foliar. The samplings were performed weekly, when the plants emitted the first trifólios through the beat cloth method. The small green bug (Piezodorus guildinii) and the brown bug (Euschistus heros) were the ones that presented the highest rates of population infestations in the present study.